METODE TAFSIR AL-QUR’AN KONTEMPORER - Annisa .; Rayhan Sutan Rabbani; Zainal Fanani (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2017)
Understanding the Qur'an can be achieved easily, using the correct interpretation method so that it will produce the intended understanding. Therefore the attention of the Ulama is very great to explore and understand the meanings contained in the Holy Qur'an. So that the various interpretations and methods of interpretation are diverse, and in that interpretation it seems clear that there is a development of the interpretation of the Qur'an and the style of thought of the interpreters themselves. This study is a literature study with a qualitative approach, because the data used are qualitative data. Literature study is research that uses data obtained from library materials, both in the form of books, magazines, journals, newspapers and other literary sources. The essence of the explanation above is that the Scientific Interpretation is proof that the verses of the Qur'an are in accordance with the proof of Science, even something that has just been discovered has been explained in the Qur'an before. Likewise from the explanation of the Hermeneutic Interpretation, we can conclude that the Hermeneutic Interpretation is the Interpreter who adopts the method of interpretation of the Western Bible which in this method is expected to give rise to the superiority of the results of the Interpretation with other methods.